2015
DOI: 10.18030/socio.hu.2015en.107
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Roma families: From hunger to inequalities

Abstract: Feeding work is complex, laborious and highly gendered in some Roma families compared to the majority population. Specifically, Roma families living in poverty are frequently large and live in substandard housing that makes feeding work more complicated. Based on ethnographic fieldwork in five different Roma settlements throughout Croatia, this paper explores how Roma households that experience severe material deprivation feed their families and their everyday experiences of food in/security and hunger. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In a study of early childhood education in Croatia, Šikić-Mićanović, Ivatts, Vojak, and Geiger-Zeman (2015) reported on multiple barriers, starting in elementary education, that contribute to poor levels of progress of Roma students: limited participation and poor levels of progress; poor pupil motivation… mirrored by low teacher expectations; lack of teacher encouragement and …challenging curricula; grade failure and repeats at crucial age stages; a real lack of teachers' intercultural competence…; unaddressed racist bullying of Roma pupils; ethnic segregation by class or pupil grouping within classes;…premature drop-out from the education system. (p.16) Following the Oršuš and others vs. the Republic of Croatia court case, the preschool funds for Roma children sharply increased in and 2013(Šikić-Mićanović et al, 2015.…”
Section: The Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of early childhood education in Croatia, Šikić-Mićanović, Ivatts, Vojak, and Geiger-Zeman (2015) reported on multiple barriers, starting in elementary education, that contribute to poor levels of progress of Roma students: limited participation and poor levels of progress; poor pupil motivation… mirrored by low teacher expectations; lack of teacher encouragement and …challenging curricula; grade failure and repeats at crucial age stages; a real lack of teachers' intercultural competence…; unaddressed racist bullying of Roma pupils; ethnic segregation by class or pupil grouping within classes;…premature drop-out from the education system. (p.16) Following the Oršuš and others vs. the Republic of Croatia court case, the preschool funds for Roma children sharply increased in and 2013(Šikić-Mićanović et al, 2015.…”
Section: The Contextmentioning
confidence: 99%
“…(p.16) Following the Oršuš and others vs. the Republic of Croatia court case, the preschool funds for Roma children sharply increased in and 2013(Šikić-Mićanović et al, 2015. Still, as Šikić-Micanovic et al (2015) reported, only 20% of Roma communities in Croatia have access to any kind of early childhood services.…”
Section: The Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Which factors have an impact on their development? I have mentioned enough-poverty, malnutrition, [and] hunger … (Šikić-Mićanović et al, 2015, p. 80) The EU Framework for a National Roma Integration Strategies Aim and the Scope of the Framework I owe the first part of the title of this paper to an e-mail exchange with my colleague Arthur Ivatts (2015) who is arguably the most experienced advocate for Roma inclusion in Europe. It is his observation, based on rich experience (and a healthy dose of cynicism), that a flurry of activity at the EU policy level can leave the impression that EU policy makers as well as international organisations are "pro-Roma and sufficiently well informed to be seriously concerned [emphasis added] about the situation of Roma (including Gypsies and Travellers)."…”
Section: Third World Conditions In Europementioning
confidence: 99%
“…• Inequality of access: while a lot of progress has been made, having access to early childhood services remains a critical issue for children from Roma communities across Europe. To give just one example, recent data from Croatia shows that only 20% of children from Roma communities have access to any kind of early childhood education service (Šikić-Mićanović et al, 2015).…”
Section: Achievements and Challenges: The Official Picturementioning
confidence: 99%